Comparison of Pregnancy Exercise Modifications in Improving the Functional Capability of Pregnant Women - Fahruddin, Sri Gunda Fahriana; Aslina, Wiwit Indriyani; Lestari, Nita Indah (Poltekkes Kemenkes Riau, 2024)
Hormonal changes in pregnant women result decreased muscle elasticity and flexibility, changes in static posture. Lower back pain in pregnant women can hinder daily functional activities. To find out physiotherapy interventions that can improve the functional abilities of pregnant women in conditions of low back pain. This research design uses randomized pre and post group design. This research used 20 subjects, divided into 2 groups. Analytical tests used paired sample t-test and independent sample t-test. Functional ability was measured using Pain Disability Index. Results of the analysis mean difference are p<0.05, which means that modified pregnancy exercise and gym ball are better than conventional pregnancy exercise in improving the functional abilities of pregnant women in NPB conditions. Pregnancy exercise and Gym ball can reduce the degree of lower back pain by training the tone of the inner transverse abdominal muscles, this can overcome NPB thereby increasing daily functional activities.